Pengaruh Dukungan Keluarga Terhadap Efektivitas Terapi Penyakit Crohn - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Milna Sari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This study examines the impact of family support on the effectiveness of Crohn's disease therapy through a meta-analysis of 18 studies involving 5,876 patients. The analysis reveals a significant positive effect (Hedges' g = 0.58, 95% CI [0.42, 0.74], p < .001) of family support on various therapeutic outcomes. The strongest effect was observed in the dimensions of quality of life (g = 0.67, 95% CI [0.48, 0.86]) and clinical remission (OR = 2.14, 95% CI [1.68, 2.73]). Furthermore, emotional support was found to have the largest effect (g = 0.63, 95% CI [0.45, 0.81]) compared to other types of family support. Mediation analysis indicated that medication adherence (indirect effect = 0.15, 95% CI [0.08, 0.22]), stress reduction (0.12, 95% CI [0.05, 0.19]), and increased self-efficacy (0.09, 95% CI [0.03, 0.15]) were significant mediators in the relationship between family support and Crohn's disease treatment efficacy. Additionally, a stronger effect of family support was observed in patients with more severe disease (Q = 4.82, p = .028) and samples with a higher proportion of females (? = 0.012, p = .03). These findings extend the work of Sewitch et al. (2001) and Moradkhani et al. (2013) by providing a more precise quantification of the effects of family support and identifying several key moderators. Unlike Trindade et al. (2017), this study consistently found a positive effect of family support on Crohn's disease therapy. The novelty of this research lies in identifying specific mechanisms and moderating factors affecting the relationship between family support and therapy effectiveness, offering a deeper understanding of the complex role of family support in Crohn's disease management.